1992
DOI: 10.1111/j.1432-1033.1992.tb17142.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipids in cestodes

Abstract: The presence of glycosphingolipids in the metacestodes of the fox tapeworm, Tueniu crassiceps, has been established. The normal-phase TLC pattern of the neutral-fraction glycolipids revealed groups of bands corresponding to homologous components of increasing sugar chain length. The three simplest glycolipid components have been isolated and their chemical constitution determined as being of the neogala series: Galpl Cer, Galp6Galpl Cer and Galp6Galfl6Galbl Cer. The ceramide tetrasaccharide fraction has been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 49 publications
2
19
1
Order By: Relevance
“…3, A and B). As expected, the enzyme displayed a (␤/␣) 8 barrel structure in which Glu 234 at the end of ␤-strand 4 and Glu 341 at the end of ␤-strand 7 could function as an acid/base catalyst and a nucleophile, respectively. Furthermore, the distance between the two catalytic Glu was separated by 5.8 Å (Fig.…”
Section: Purification and Partial Amino Acid Sequence Of Egalc-supporting
confidence: 74%
See 2 more Smart Citations
“…3, A and B). As expected, the enzyme displayed a (␤/␣) 8 barrel structure in which Glu 234 at the end of ␤-strand 4 and Glu 341 at the end of ␤-strand 7 could function as an acid/base catalyst and a nucleophile, respectively. Furthermore, the distance between the two catalytic Glu was separated by 5.8 Å (Fig.…”
Section: Purification and Partial Amino Acid Sequence Of Egalc-supporting
confidence: 74%
“…Eight residues essential for the catalytic reaction in microbial and animal endoglycoceramidases were all conserved in the deduced amino acid sequence of the novel enzyme. Homology modeling of the enzyme using endocellulase E1 as a template revealed that the enzyme displays a (␤/␣) 8 barrel structure in which Glu 234 at the end of ␤-strand 4 and Glu 341 at the end of ␤-strand 7 could function as an acid/base catalyst and a nucleophile, respectively. Site-directed mutagenesis of these glutamates resulted in a complete loss of the activity without a change in their CD spectra.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gal repeats appear to be cestode-specific motifs. In glycosphingolipids isolated from the adult stage of Metroliasthes coturnix, metacestodes of Taenia crassiceps and E. multilocularis Gal␤1-4Gal and Gal␤1-6Gal sequences have been demonstrated, and the latter motif was suggested to constitute an epitope recognized by sera from alveolar echinococcosis patients (17)(18)(19). In this context, it would be informative to determine the epitope recognized by the MAbG11 as used in this study for the purification and detection of the Em2(G11) antigen.…”
Section: Discussionmentioning
confidence: 94%
“…These saccharides were specifically found in flatworms, platheliminthes, such as tapeworm and round worm, and in annelida, such as earthworms (Dennis et al, 1992;Hada et al, 2001). Recently, however, these oligosaccharides were also discovered in zygomycetes such as Rhizopus (Aoki et al, 2004) and thus they are much more widely distributed than had originally been thought.…”
Section: Discussionmentioning
confidence: 96%